Study of the scale effect on the resistance components and the flow field around the tanker ship - Abbas, Nawar (Latakia University Journal -Engineering Sciences Series, 2025)
Historically, the field of marine engineering has relied on a combination of model testing and similarity laws, known as the extrapolation approach, which relies on using a set of approximate relationships to predict the power requirements of a real ship. Several problems with the extrapolation approach have been identified as the values ​​obtained through these approximate relationships are not accurate compared to reality, but due to the lack of accurate alternative relationships, it has continued to be used up to the present day. This research focuses on studying the effects of scale on the basic components of the resistance of oil ships (tanker) and the flow field around them using a CFD approach. The study was conducted on the oil tanker KVLCC2 using six different scales at a fixed value of Froude number Fr = 0.142, which is the value corresponding to the nominal speed of the ship. To analyze the effect of scale on resistance, the total resistance components were divided into individual components and the ratio of the individual resistances to the total resistance of each scale was calculated and then compared with each other. The numerical results were compared with experimental data to verify their validity. The comparison demonstrated the accuracy of the setup and the numerical grid used. Finally, we studied and analyzed the effect of the scale on the velocity, pressure and vortices fields around the hull, as these are the basic parameters that must be studied in detail when designing any ship.